Genome-wide genetic screen identified the link between dG9a and epidermal growth factor receptor signaling pathway in vivo. - Shimaji, K.; Konishi, T.; Yoshida, H.; Kimura, H.; Yamaguchi, M. (Experimental Cell Research, 2016)
G9a is one of the histone H3 Lys 9 (H3K9) specific methyltransferases first identified in mammals. Drosophila G9a (dG9a) has been reported to induce H3K9 dimethylation in vivo, and the target genes of dG9a were identified during embryonic and larval stages. Although dG9a is important for a variety of developmental processes, the link between dG9a and signaling pathways are not addressed yet. Here, by genome-wide genetic screen, taking advantage of the rough eye phenotype of flies that over-express dG9a in eye discs, we identified 16 genes that enhanced the rough eye phenotype induced by dG9a over-expression. These 16 genes included Star, anterior open, bereft and F-box and leucine-rich repeat protein 6 which are components of epidermal growth factor receptor (EGFR) signaling pathway. When dG9a over-expression was combined with mutation of Star, differentiation of R7 photoreceptors in eye imaginal discs as well as cone cells and pigment cells in pupal retinae was severely inhibited. Furthermore, the dG9a over-expression reduced the activated ERK signals in eye discs. These data demonstrate a strong genetic link between dG9a and the EGFR signaling pathway.